A systematic review of the green tea effects on anthropometric parameters of PCOS patients - Azahari, Nuraniza; Mokhtar, Aisyah (IIUM Press, 2023)
Introduction: Polycystic Ovarian Syndrome (PCOS) is a prevalent endocrine illness affecting reproductive-aged women that is characterized by irregular menstruation periods, infertility, hirsutism and obesity. Natural therapies, such as extract green tea supplementation, have recently received interest owing to their possible therapeutic properties. However, only a few studies linked green tea with PCOS patients. Hence, this study aimed to review the effects of green tea on anthropometric parameters of patients with polycystic ovarian syndrome (PCOS). Method: Articles were identified through PubMed, Science Direct, Scopus and Google Scholar electronic databases based on PCOS OR “polycystic ovar* syndrome” AND “green tea” OR “Camelia Sinensis” AND “anthropomet* parameters” OR “weight” OR “body mass index (BMI)” keywords and were included if they met the following criteria: in-vivo studies, female, studies of green tea, PCOS patient, English paper and article from year 2006 until 2023. The reviewing process was conducted according to the Preferred Reporting Items for Systematic and Meta- Analyses (PRISMA 2020) method. Results: A total of 34 relevant abstracts were screened and 5 full-text articles were reviewed. The findings found that green tea have a significant effect in reduction of weight, BMI, waist circumference and body fat percentage. The recommended daily dose is ranging from 500 mg to 540 mg while the working duration is 12 weeks. Conclusions: Green tea supplementation may have some potential advantages for weight loss and maintenance in those with polycystic ovarian syndrome (PCOS) depending on the amount and period of consumption. Nonetheless, more clinical studies are needed to corroborate these findings and identify the proper use of abstract green tea as an additional treatment for PCOS control.